Critical Thinking Measurement Methods in Higher Education: A Bibliometric Analysis - Arfiani, Yuni; Wiyanto, Wiyanto; Ridlo, Saiful (Universitas Negeri Semarang, 2024)
Critical thinking skills are crucial in modern society. This research aims to provide a general overview of recent developments in research methods for measuring critical thinking skills in higher education. It is based on a bibliometric analysis of journal articles published in the Scopus database, with the goal of identifying scientific gaps and providing a reference for further research. The methodology employed includes bibliometric analysis using VOSviewer and Biblioshiny software. The results indicated a growing trend in research focused on measuring critical thinking skills. Several topics and keywords have emerged that could serve as a foundation for future studies, along with trends in research methods for assessing critical thinking skills in higher education. The research concluded that bibliometric analysis offers valuable insights into developing research on measuring critical thinking and its methods, paving the way for further investigations. Notably, topics related to undergraduate students, critical thinking skills, and active learning potentially yield significant novel contributions if explored in future research.